2006
DOI: 10.1128/aem.72.1.378-383.2006
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Monochloramine into a Municipal Water System: Impact on Colonization of Buildings by Legionella spp

Abstract: Legionnaires' disease (LD) outbreaks are often traced to colonized potable water systems. We collected water samples from potable water systems of 96 buildings in Pinellas County, Florida, between January and April 2002, during a time when chlorine was the primary residual disinfectant, and from the same buildings between June and September 2002, immediately after monochloramine was introduced into the municipal water system. Samples were cultured for legionellae and amoebae using standard methods. We determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
75
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 15 publications
9
75
0
Order By: Relevance
“…The water sampling procedure was identical to that used for BCV, except that shower water samples were collected when available and biofilm samples were collected from taps and shower heads by swabbing the inner surfaces with sterile cotton. These additional samples facilitated comparison with a previous CDC study (54).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The water sampling procedure was identical to that used for BCV, except that shower water samples were collected when available and biofilm samples were collected from taps and shower heads by swabbing the inner surfaces with sterile cotton. These additional samples facilitated comparison with a previous CDC study (54).…”
Section: Methodsmentioning
confidence: 99%
“…Details of PCF were reported in a previous U.S. Centers for Disease Control (CDC) study (54), except that the source water has been adjusted to a blend of surface, ground, and desalinated water (at the time of the previous CDC study, the source water was 100% groundwater). Sampling took place in May 2011, targeting eight sites that were positive and seven sites that were negative for Legionella in the previous CDC study (54). Among the eight Legionella-positive sites, three were reported positive only when chlorine was used as the disinfectant and negative following the switch to chloramination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since NTM species can grow under oligotrophic conditions (5, 23), distribution of drinking water without a disinfection residual might increase the risk of NTM growth during distribution of the drinking water. On the other hand, studies have demonstrated that certain NTM species are especially resistant to monochloramine and that shifts from chlorine to monochloramine disinfection in drinking water treatment resulted in enhanced numbers of NTM in the drinking water distribution system (24)(25)(26). Research in the 1980s demonstrated the occurrence of M. kansasii in drinking water from the Rotterdam area in the Netherlands (27).…”
mentioning
confidence: 99%